Effects of various colorants on self-dyed silk properties: Aspects of color, Thermal stability, Morphology, and Degumming - Trần Nguyễn, Tú Uyên; Phan Ngoc, Hung; Nguyen Minh, Ngoc Son; Hoang , Thanh Thao; Bui, Mai Huong (Vietnam Journal of Science and Technology, 2024)
The process of dyeing has resulted in significant water consumption and wastewater discharge by the textile industry. The study’s goal is to create and characterize self-dyed silks by feeding techniques with various natural and synthetic colorants in order to decrease textile environmental risks and improve the added value of silk. In this study, Bombyx mori was given mulberry leaves that had been dyed using nanocurcumin derived from turmeric powder, as well as dyestuffs from Caesalpinia sappan, Acid Red 88, and Basic Red 13. The colorimetric, morphological, and thermal characteristics of both pristine and degummed self-dyed silks were thoroughly assessed using the CIELab color, color strength K/S, scanning electron microscopy (SEM), and thermal gravimetric analysis (TGA). Consequently, Acid Red 88 greatly improved the coloring effectiveness of silks when compared to another natural dye and basic red. After all of the self-dyed silk was degummed, it was discovered that it was dispersed mainly in the sericin layer rather than the fibroin. The surface morphology and temperature properties of silk threads were also changed by the self-dyeing process. This study proposed waterless and sustainable silk coloration methods with various natural and synthetic colorants, which will help to address the health and environmental dangers connected with the dyeing industry, as well as the increasing demand for greener and more sustainable long-term development choices. Besides, the effects of degumming process on self-dyed silks were also fully depicted.